PERAN SELF CONTROL TERHADAP PERILAKU AGRESI ORANG TUA KEPADA ANAK - aswar, Aswar aswar; Pusadan, Faizal Ramadan (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2020)
Children are often forced to follow the wishes of their parents, which often leads to aggressive behavior, so that self-control is needed to minimize aggression. This research uses a quantitative approach. The population of this research is all citizens of Makassar who are married and have children. Determination of the sample with the krejcie and Morgan tables, the total sample was 384 respondents. Methods of data collection through a questionnaire with a Likert scale model, and hypothesis testing with simple regression analysis. The results obtained were a significance value of 0.000 <0.05. With a regression coefficient value of - 0.435 and an R Square value of 0.049 or equal to 4.9%. So that the results of this study state that there is a significant negative effect of self control on the aggression behavior of parents towards children in Makassar City. This means that if self-control increases, the aggression behavior of parents towards children will decrease, and vice versa.